Influence of supplementation method on forage use and grazing behavior of beef cattle grazing bluestem range - S.D. Brandyberry; R.C. Cochran; E.S. Vanzant; T. DelCurto; J.E. Schneider; L.R. Corah (Kansas Agricultural Experiment Station Research Reports, 1990)
Fifteen ruminally and 12 esophageally fistulated steers were used in two 28-d trials (late summer and early winter) to determine the influence of method of supplementation on forage use and grazing behavior. 1Ceatments were: 1) self-feeding supplement with salt to limit intake; 2) daily hand-feeding supplement and salt; 3) daily hand-feeding supplement without salt. Forage intake was not affected by season or supplementation method; however, total diet organic matter digestibility was higher in the late summer (P<.01) and lower when steers received supplement without salt (P<.05). Supplementation method did not affect the time that animals spent grazing or the distance travelled; however, both were greater (P<.01) during the summer period. Self-feeding supplement did not appear to adversely affect forage use in grazing beef steers.
Keywords: Cattlemen' s Day; 1990; Kansas Agricultural Experiment Station contribution; no. 90-361-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 592; Beef; Protein supplements; Rangelands; Grazing behavior; Stockers